2015
DOI: 10.1038/srep08976
|View full text |Cite
|
Sign up to set email alerts
|

“Roar” of blaNDM-1 and “silence” of blaOXA-58 co-exist in Acinetobacter pittii

Abstract: Acinetobacter pittii 44551 was recovered from a patient with gout combined with tuberculosis and was found to harbor the carbapenemase genes blaNDM-1 and blaOXA-58 on two different plasmids pNDM-44551 and pOXA58-44551, respectively. pNDM-44551 displayed high self-transferability across multiple bacterial species, while pOXA58-44551 was likely co-transferable with pNDM-44551 into A. baumannii receipts. pNDM-44551 was a close variant of the previously characterized pNDM-BJ01, and the blaNDM-1 gene cluster was ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…An imipenem-EDTA double-disc synergy test and a modified Hodge test were used to screen for the presence of Metallo-β-lactamases(MBLs) and carbapenemases, respectively, and were analyzed according to CLSI guidelines (Zhou et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…An imipenem-EDTA double-disc synergy test and a modified Hodge test were used to screen for the presence of Metallo-β-lactamases(MBLs) and carbapenemases, respectively, and were analyzed according to CLSI guidelines (Zhou et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…The genome ACN21 was devoid of bla OXA-23 , while the presence of bla NDM-1 and bla OXA-420 could be encoding for carbapenem resistance. In ACN21, bla NDM-1 resides in chromosome and bla OXA-420 in plasmids whereas previous studies reported the co-presence of bla NDM and bla OXA-58 on the same plasmid [31][32][33][34]. In CIAT 758, bla OXA-58 was carried on the plasmid (Table 1).…”
Section: Resistance Determinantsmentioning
confidence: 95%
“…11,[19][20][21] In addition, the genes encoding bla NDM and bla OXA are known to be carried on some mobile genetic elements that inserted into the chromosome or plasmids, and it is suspected the mechanism of horizontal gene transfer (HGT) promotes the exchange of resistance genes among pathogenic microorganisms isolated from the clinical, environmental samples, and food animals. 11,[22][23][24][25] In this study, we mainly characterized the genetic feature of a carbapenems resistant strain Acinetobacter johnsonii Acsw19 isolated from municipal sludge. This strain was found to carry two copies of bla NDM-1 , cmlB1-like gene, and bla OXA-211 -like gene along with other 8 antimicrobial resistance genes, three plasmids, 15 genomic islands and 8 prophages.…”
Section: Introductionmentioning
confidence: 99%